JUSTIFICATION FOR THE CHOICE OF MOBILE APPLICATIONS FOR CREATING AND ORGANIZING A FASHIONABLE WARDROBE - ZAKHARKEVICH, OKSANA; KOSHEVKO, JULIA; LYSENKO, SERGII (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In recent years, there has been a noticeable trend in the research and development of mobile applications for working with consumers’ wardrobes. Several applications have similar functions. The applications can be found on the platforms of Google Play, App Store, and others. However, all these works are aimed primarily at meeting the needs of end-users of garment products. Thus, the main goal of the current research is to provide a reasonable selection method to choose a mobile application for the specific situation. The performed comparative analysis of mobile applications for creating a capsule wardrobe allows one to reasonably choose a mobile application for use in the learning process, as well as in the domain of the real economy besides operating by end-users themselves. In this case, in a specific project or a specific educational situation, it is advisable to form a list of additional requirements that are key to solving this problem. The formulated working hypothesis of the research on the possibility of adapting existing mobile applications to the production/training needs of the apparel industry has been confirmed by the example of several applications. The use of ready-made mobile applications that already exist in the market of mobile technologies, allows companies to offer technology that does not require any costs for its implementation; it does not require any additional equipment - almost every employee already has a smartphone. In addition, such technology does not require additional training. The same thesis applies to education: no additional equipment is needed to attract such technology. Higher education students can take advantage of automation even in classrooms that are not equipped with computers. The implementation of digital tools such as mobile applications in the educational process will increase the interest and involvement of students in the learning process. Customizing mobile applications that are already on the mobile market will create a transition between the learning process and specific project situations in the workplace. It will provide the young specialist with a digital tool that avoids mechanical errors and facilitates the decision-making process.